Reflections on Cultural Portfolios: Reassessing Assessment Through Student Voice and Agency in Language Education - George, Angela; Friedman, Rachel; Buonocore, Eleonora (Imagining SoTL, 2026)
This reflection explores the design and implementation of cultural learning portfolios as alternative assessments in undergraduate language courses. Responding to tensions between traditional assessment practices and the complex, lived nature of language-and-culture learning, we replaced standardized tests and essays with reflective, multimodal portfolios. These portfolios allowed students to engage with cultural experiences of their choosing and demonstrate growth through multilingual and cross-cultural reflection. Drawing on theoretical frameworks from relational and participatory pedagogy (Gachago et al., 2022) and plurilingual assessment (Bonvino & Cortés Velásquez, 2024), we illustrate how portfolios reposition students as co-constructors of knowledge. Through survey data (Likert-scale and open-ended questions) and interviews with students in Arabic, German, Italian, and Spanish courses, we reflect on how this assessment model reshaped our understanding of what meaningful assessment can look like in language education. Rather than offering a prescriptive model, we share insights from our experience. Both the successes and challenges invite continued dialogue about assessment as a relational, reflective, evolving practice.